Thirty years of economic transition in the former Soviet Union: Microeconomic and institutional dimensions - Marek Dabrowski (Russian Journal of Economics, 2023)
The post-communist transition in the former Soviet Union (FSU) cannot be considered entirely successful, especially in the political and institutional spheres. Nevertheless, in the economic sphere, the transition process succeeded in rebuilding the foundations of market economies based on private ownership by the early 2000s, even if the adopted policies and institutions have proved suboptimal and distortive in many countries. The transition experience in the FSU region has demonstrated a correlation between political and economic reforms, with a strong impact of the former on the latter. The deficit of democracy, civil freedoms and the rule of law has negatively impacted the course of the economic transition, causing significant delay, distortions and partial reversals.